Financial Accounting and Tax Management under the Background of the Internet - Zheng, Wen (Journal of Theory and Practice of Social Science, 2023)
With the rapid development of Internet finance, the fields of financial accounting and tax management show new characteristics, which further promotes the reform and development of financial accounting and tax management. Based on this, starting from the current problems of Internet financial accounting and tax management, this paper discusses the countermeasures to strengthen Internet financial accounting and tax management. The so-called learning activity is a series of teaching and learning activities in a specific environment. It includes both teaching and learning. Using a study plan to summarize can better reflect an attitude toward students' study plans. There are seven main perspectives on discussing teaching and learning activities in relevant translated works. They are the Angle of teaching content, the Angle of learning or cognitive psychological process, the Angle of teaching principle, the Angle of teaching mode, the Angle of teacher- student relationship, the Angle of stage or process and the Angle of discipline. In the past 20 years, the curriculum and teaching reform of primary education in China has taken teacher-student as the starting point, but its practical effect in curriculum implementation is worth rethinking. At the same time, based on the study of translated works, the author analyzes the exploratory learning activities under the situation of concise problems.